Due regard obligations in the law of the sea convention - Fasia, EE (2024)
thesis explores the meaning of the term ‘due regard’ in the context of the Law of the Sea Convention (‘LOSC’ or ‘the Convention’). It seeks to provide clarity on the range of due regard obligations (DROs) in the Convention and analyse their interpretation and application. Additionally, going beyond the express LOSC provisions embedding due regard obligations, the thesis considers whether due regard permeates the Convention as an organising principle. The Convention includes several provisions that use terms such as ‘due regard,’ ‘reasonable regard,’ ‘regard,’ ‘undue interference,’ and ‘unjustifiable interference’ in order to accommodate competing State interests at sea. The content and function of these obligations have not been thoroughly and systematically studied and their application in practice can be problematic due to their indeterminate stipulation. Practical problems can potentially arise every time that multiple activities coexist and compete in the same maritime space or adjacent maritime spaces. Lack of clarity in the interpretation of DROs hinders their effective application to the detriment of individual States’ or communal interests. The thesis tests the presumption that DROs within the LOSC are effective and meaningful in accommodating the tension and competition between various equally important interests at sea. Through a thorough analysis and systematization of DROs the thesis reveals the different methods of accommodation of competition embodied in the Convention, aiming to help interpreters in understanding the precise scope of the relevant obligations, the processes to be followed, and the outcomes that are expected by their application. The research demonstrates that DROs in the LOSC are interstitial obligations. This means that DROs are context-dependent and do not possess independent substantive content, functioning rather as ancillary obligations that enable the effective operation of certain rules within the Convention. In situations of co-existing rights and obligations at sea, DROs provide the way to harmonize these coexisting rules through balancing or moderation. Balancing DROs entail a reasonableness test that allows an ad hoc evaluation of various proposed criteria, while moderating DROs operate as restrictions to certain rules and impose a duty on States to consider specific factors and act within defined limits. Further, the analysis on interstitiality demonstrates that DROs serve as an organising principle of the LOSC, facilitating the consideration even of issues not explicitly regulated in the Convention. Lastly, the thesis makes a normative proposition that due regard should be viewed as a way to resolve broader law of the sea questions beyond the realm of the LOSC.